Asymmetry of Tropical Pacific Precipitation Responses to El Niño and La Niña in a Changing CO 2 Pathway - Wen Zhang; Weichen Tao; Gang Huang; Ping Huang; Kaiming Hu; Ya Wang; Haosu Tang; Suqin Zhang (International Journal of Climatology, 2025)
In the tropical Pacific, El Niño (EN) typically causes positive precipitation anomalies further east than La Niña (LN)'s negative anomalies. This study constructs an idealised scenario of symmetrical CO 2 ramp‐up (RU) and ramp‐down (RD) phases to analyse the changes in asymmetric precipitation response to EN and LN. The results reveal that, during the CO 2 RD phase, tropical Pacific precipitation anomalies in EN and LN both shift more eastward and southward compared to the RU phase, but with more pronounced shifts in EN than LN. These structural changes in precipitation anomalies are primarily driven by the dynamic component associated with changes in circulation anomalies, which cannot be explained by variations in sea surface temperature (SST) anomalies. The spatial pattern of climatological SST changes between the CO 2 RD and RU phases exhibits an EN‐like warming structure, particularly extending southward, which enhances low‐level moisture and weakens atmospheric stability. Consequently, precipitation during EN responds more strongly to SST anomalies in this region, accompanied by eastward and southward shifts. While LN partially offsets the impact of the climatological warming pattern and results in less pronounced shifts, thereby contributing to the structural changes in the EN–LN asymmetry of precipitation anomalies.